Relationship between Chlamydia Seropositivity and Presence of Symptoms of Sexually Transmitted Infections among Students of Nnamdi Azikiwe University, Awka (Journal of Biomedical Investigation, 2009)
In an attempt to determine the prevalence of Chlamydia antibodies among students of higher institution, 84 students of a University in South-Eastern Nigeria were —screened for Chlamydia seropositivity. Volunteers were selected and questionnaires distributed. The questionnaires determined demographic data, level of sexuality, marital status, health care patronage and symptomatic presentation among the students selected. Of 84 students recruited, 26(31%) were males while the rest, 58(69%) were females. The antibody test was carried out using worldwide diagnostics Chlamydia IgG quantitative test. The overall prevalence of Chlamydia seropositivity among the population studied was 6.0%, females being more affected (6.9%) than males (3.8%). Frequency of symptom was higher among females 41(89.1%) than was the case among males 5(10.9%) in all the 46 symptomatic cases investigated. Lower abdominal pain and discharge were more frequently associated with Seropositivity. The highest incidence of C. trachomatis Seropositivity was among students who had begun sexual activity under 25 years of age, had multiple sexual partners and with little or no access to health care.
Keywords: Chlamydia; Population; Frequency